Natural Science Visual Model Videos for Online Learning: Effect on Students’ Achievement in Constructivist Approach - Alif Syaiful Adam; Tomy Andre Ansyah; Widya Rohmawati; Parno Parno; Endang Purwaningsih (Indonesia Approach Education, 2021)
Natural Science is a subject on junior high school level, consist of Physics and Biology. As the characteristic of contextual, natural science has many parts to be explained by observation, presenting the real object both in reality or virtually. As the pandemic era, the learning process difficult to held the real presenting, and virtual approach is the answer of this challenge. Video is one of the teaching and learning media for online learning. In visual model, the video completes with the visualization of particular process or particular object which difficult to direct observe like planets in universe. Furthermore, this particular study aimed to measure the students’ achievement and compare to traditional learning held in offline setting. The students’ achievement represents with the final test in the end of semester. The variables measured in a whole semester with 119 students in junior high level. Besides, the semester with videos for online learning compare to the achievement in the offline semester on same students. As the results, the students’ achievement with the set of visual model videos better than the traditional instruction. After more, this finding can use as the alternative method in online learning due to the continuing pandemic era in Indonesia with extend the study from home program.